EVALUATION OF E-LEARNING TOOLS AND TECHNIQUES AT ENGLISH DEPARTMENTS: CASE OF BENINESE NATIONAL UNIVERSITIES - EGOUNLETI, Pédro Marius; IWIKOTAN, K. ETIENNE; HOUNHANOU AR, Arlette J. Viviane (My University, 2021)
With the outbreak of the Covid 19, a great number of universities in both developed and developing countries around the world have resorted to electronic management systems to maintain their teaching and learning programs.The universities of the republic of Benin are no exception. Despite the important investments by the Beninese government and the potential of learning management systems to support both blended learning and learning that is entirely delivered online, the majority of LMS-supported e-learning initiatives do not fulfill their objectives; they fail, either totally or partially. To investigate the underlying causes of failure, this study was conducted through interviews with 6 lecturers and 3 key e-learning personalities involved in elearning initiatives in 3 English departments of 3 national universities in the republic of Benin (Abomey Calavi, Adjarra and Parakou). Moreover, a structured questionnaire has been designed and sent to 12 students’ prefects .The analysis of the data collected revealed that some of the most probable causes of this failure were: insufficiency of financial investments, lack of preparation, high ICT illiteracy rates among the student community; low comfort levels with technology; usability issues of learning management systems; poor marketing strategies; ineffective maintenance strategies and insufficient user/technical support. In order to make e-learning management systems yield its expected results, EFL students, teachers and universities authorities must be informed about these causes of failure and further research towards more successful deployment of learning management systems in Beninese universities must be made.
Keywords: Learning Management Systems; E-learning; Evaluation